The role of prenatal, obstetric, and post-partum factors in the parenting stress of mothers and fathers of 9-month old infants - Karen Matvienko-Sikar; Gillian Murphy; Mike Murphy (Journal of Psychosomatic Obstetrics and Gynecology, 2018)
Introduction: The aim of this paper was to examine the role of perinatal, obstetric and post partum factors on maternal and paternal stress. It will present the first examination of the role of prenatal, obstetric, post-partum, and demographic variables in parenting stress for mothers and fathers at 9 months. Methods: Data from 6821 parental dyads of 9-month-old infants were extracted from the Growing Up in Ireland National Longitudinal Study of Children. Participants completed the Parental Stress Scale, the Dyadic Adjustment Scale, the Quality of Attachment Sub-scale from the Maternal and Paternal Postnatal Attachment Scales, and a single item health status question from the Short Form 12 Health Survey. Information on prenatal care, pregnancy complications, obstetric outcomes, infant health, and participant demographics were also collected. Separate hierarchical linear regressions were conducted for mothers and fathers Results: Mothers reported higher levels of parenting stress than fathers (p < 0.001). Maternal parenting stress was predicted by attachment, own health status, average sleep, occupation, household income, and having a very rapid labor. Paternal parenting stress was predicted by attachment and own health status. Discussion: A range of perinatal factors was associated with an increased risk of higher parenting stress at 9 months post-partum and the roles of these factors differ between mothers and fathers. These findings are important for predicting and reducing risk of parenting stress in both genders.